Evaluating User Interfaces in E-Learning Satisfaction Using EUCS Method - Cindy Angrayni; Erwin Setiawan Panjaitan (Yayasan Cita Cendekiawan Al Khwarizmi, 2025)
This study investigates how User Interface elements affect student satisfaction with E?Learning platforms among junior high school, senior high school, and vocational high school students in Medan by adopting the End User Computing Satisfaction model augmented with a dedicated User Interface quality construct. It examines Content, Accuracy, Format, Ease of Use, Timeliness, and overall Interface Perception as predictors of End User Computing Satisfaction. Data were gathered via questionnaires administered to students actively using E?Learning applications across these three school levels in Medan and Structural Equation Modeling was employed to explore the complex interrelationships among these constructs. Results reveal that Accuracy, Format, Ease of Use, and Timeliness each exert positive and significant influences on perceived Interface quality, with Ease of Use contributing most strongly, while Content presentation alone does not significantly affect perceptions. Furthermore, perceived Interface quality demonstrates a very strong and significant impact on End User Computing Satisfaction. These findings indicate that in the context of Medan’s junior high school, senior high school, and vocational high school digital learning environments, intuitive usability, clear visual formatting, information accuracy, and prompt delivery are critical drivers of student satisfaction. This study underscores the need for E?Learning developers and educational policymakers to prioritize intuitive, reliable, and responsive interface designs and recommends that future research broaden sample coverage to additional regions, compare multiple E?Learning platforms, and adopt longitudinal designs to capture how Interface element effects on student satisfaction evolve over time.